2006
DOI: 10.1246/cl.2006.600
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Ionic Liquid by Scanning Electron Microscope

Abstract: It has been discovered that ionic liquid can be observed by a scanning electron microscope without accumulation of electron charges, allowing SEM observation of insulating specimens wetted with ionic liquid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
117
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 170 publications
(122 citation statements)
references
References 22 publications
4
117
0
Order By: Relevance
“…3A). Kuwabata et al (2006) reported the direct observation of IL by SEM. Direct SEM observation of pollen grains pretreated with a 33% (v/v) ethanolic IL solution showed some degree of reticulate structure on the surface of the grains (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A). Kuwabata et al (2006) reported the direct observation of IL by SEM. Direct SEM observation of pollen grains pretreated with a 33% (v/v) ethanolic IL solution showed some degree of reticulate structure on the surface of the grains (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ILs can be utilized for studies under vacuum conditions because of their peculiar physicochemical properties, which include negligible vapor pressure and high ionic conductivity (Armand et al, 2009;Rogers, 2007;Rogers and Seddon, 2003;Seddon, 2003;Tsuda et al, 2011a). Recently, Kuwabata et al (2006) showed that ILs could be observed by SEM without the electroncharge accumulation from the so-called charge-up effect, although ILs possess ionic conductivity. It was subsequently demonstrated that IL-treated specimens swollen with water could be observed by SEM without the laborious pretreatment processes (Arimoto et al, 2008c;Dwiranti et al, 2012;Ishigaki et al, 2011a, b, c;Takahashi et al, 2013;Tsuda et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 An alternate approach proposed by Kuwabata et al is the use of non-volatile electrolytes (i.e., ionic liquids) to coat a wet specimen for SEM observation. 15 SEM observation under low vacuum by cooling wet specimens to prevent evaporation of the solvent has also been reported. 16 However, none of the above techniques allow for in situ observation of dynamic processes such as solvent evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, we have succeeded in SEM observation of RTIL itself without charging behavior. 8 Subsequently a thin RTIL liquid layer spread on insulating materials was found to work as a conductive layer when the materials are observed by SEM. 912 Now there is a growing trend of the articles on the novel analytical technique combined with RTIL and SEM.…”
Section: Introductionmentioning
confidence: 99%